Emergency Medicine Obstetrics and Gynecology: A Case-Based Curriculum for Residents - Shannon M. Burke; Thaddeus Schmitt; Polly Kennedy; Brittany Kotek; James N. Wolfe; Corlin Jewell; Kaitlin A. Ray; Benjamin H. Schnapp (Association of American Medical Colleges, 2023)
Introduction Millions of patients present to US emergency departments every year with OB/GYN concerns. Emergency medicine trainees must be adequately prepared to care for this population, regardless of how commonly they appear in the training environment. We used active learning and gamification principles in this curriculum to increase learner engagement and participation in the material. Methods We chose OB/GYN topics based on review of Tintinalli's OB/GYN content and the American Board of Emergency Medicine's Model of Clinical Practice. Each session comprised a case-based lecture and review questions using the game-based Kahoot! online software. Pre- and postcurriculum surveys assessed residents' confidence in caring for emergent OB/GYN pathologies on a 5-point Likert scale. We designed survey questions assessing the first level of Kirkpatrick's levels of training evaluation; these questions were reviewed and revised by the department's Medical Education Scholarship Committee for validity. Results A mean of 18 residents attended each session. Seventy-six percent of residents (26 of 34) completed the precurriculum survey, 67% (23 of 34) completed the postcurriculum survey, and 44% (15 of 34) completed both. For all respondents, mean reported confidence with curriculum topics increased from 3.5 to 4.0 (p < .05). For residents completing both surveys, confidence increased from 3.4 to 4.0 (p < .01). Discussion Application of this curriculum significantly improved learner confidence in targeted OB/GYN topics. Future directions could include evaluating curricular impact at higher levels in the Kirkpatrick model, extending sessions to include more time for interaction, and adding suggested readings.